Oxytocin ameliorates oxidative colonic inflammation by a neutrophil-dependent mechanism - YEGEN, BERRAK; ERCAN, FERİHA; ŞENER, GÖKSEL (ELSEVIER SCIENCE INC, 2005)
Oxytocin (OT), a nonapeptide produced in the paraventricular and the supraoptical nuclei in the hypothalamus has a wide range of effects in the body. However, the role of OT on the gastrointestinal (GI) tract has to be settled. OT may participate in the regulation of motility, secretion, blood flow, cell turnover and release of neurotransmitters and/or peptides in the GI tract, possesses antisecretory and antiulcer effects, facilitates wound healing and is involved in the modulation of immune and inflammatory processes. The present work was conducted to assess the possible therapeutic effects of OT against the acetic acid-induced colonic injury in the rat. Methods: Colitis was induced by intracolonic administration of acetic acid (5%) in Sprague-Dawley rats (200-250 g). Either saline or OT (0.5 mg/kg) was injected subcutaneously, immediately after the induction of colitis and repeated two times a day for 4 days. On the 4th day, rats were decapitated and distal 8 cm of the colon were removed for the macroscopic and microscopic damage scoring, determination of tissue wet weight index (Wl), malondialdehyde (NIDA) levels, an end product of lipid peroxidation; glutathione (GSH) levels, a key antioxidant; and myeloperoxidase (MPO) activity, as an indirect index of neutrophil infiltration. Colonic collagen content, as a fibrosis marker was also determined. Lactate deydrogenase (LDH) and tumor necrosis factor-alpha (TNF-alpha) levels were assayed in serum samples. In the acetic acid-induced colitis, macroscopic and microscopic damage scores, WI, MDA and MPO levels were significantly increased, while GSH levels were decreased when compared to control group (p < 0.05-<0.001). Treatment with OT abolished the colitis-induced elevations in damage scores, WI, MDA and MPO levels and restored the GSH levels (p<0.05-0.001). Similarly. acetic acid increased the collagen content of colonic tissues and OT-treatment reduced this value to the level of the control group. Serum LDH and TNF-a levels were also elevated in the acetic acid-induced colitis group as compared to control group, while this increase was significantly decreased by OT treatment. The results suggest that OT, which improves the antioxidative state of the colonic tissue and ameliorates oxidative colonic injury via a neutrophil-dependent mechanism, requires further investigation as a potential therapeutic agent in colonic inflammation. (C) 2004, Elsevier Inc. All rights reserved.
Keywords: oxytocin; colitis; oxidative damage; inflammation; neutrophils; REACTIVE OXYGEN METABOLITES; ATRIAL-NATRIURETIC-PEPTIDE; ACID-INDUCED COLITIS; ACETIC-ACID; GASTROINTESTINAL-TRACT; GROWTH-HORMONE; FREE-RADICALS; IN-VITRO; RATS; VASOPRESSIN